Long-read genome and RNA sequencing resolve a pathogenic intronic germline LINE-1 insertion in APC - Alexandra A. Baumann; Lisanne I. Knol; Marie Arlt; Tim Hutschenreiter; Anja Richter; Thomas J. Widmann; Marcus Franke; Karl Hackmann; Sylke Winkler; Daniela Richter; Isabel Spier; Stefan Aretz; et al. (npj Genomic Medicine)
Abstract Familial adenomatous polyposis (FAP) is caused by pathogenic germline variants in the tumor suppressor gene APC. Confirmation of diagnosis was not achieved by cancer gene panel and exome sequencing or custom array-CGH in a family with suspected FAP across five generations. Long-read genome sequencing (PacBio), short-read genome sequencing (Illumina), short-read RNA sequencing, and further validations were performed in different tissues of multiple family members. Long-read genome sequencing resolved a 6 kb full-length intronic insertion of a heterozygous LINE-1 element between exons 7 and 8 of APC that could be detected but not fully resolved by short-read genome sequencing. Targeted RNA analysis revealed aberrant splicing resulting in the formation of a pseudo-exon with a premature stop codon. The variant segregated with the phenotype in several family members allowing its evaluation as likely pathogenic. This study supports the utility of long-read DNA sequencing and complementary RNA approaches to tackle unsolved cases of hereditary disease.